Early Goal-Directed Therapy in Severe Sepsis and Septic Shock: A Meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials. (May 2018) - Lu, Yao; Zhang, Han; Teng, Fang; Xia, Wen-Jun; Sun, Gui-Xiang; Wen, Ai-Qing
Introduction: The Surviving Sepsis Campaign guidelines recommend early goal-directed therapy (EGDT) for the resuscitation of patients with sepsis; however, the recent evidences quickly evolve and convey conflicting results. We performed a meta-analysis to evaluate the effect of EGDT on mortality in adults with severe sepsis and septic shock. Methods: We searched electronic databases to identify randomized controlled trials that compared EGDT with usual care or lactate-guided therapy in adults with severe sepsis and septic shock. Predefined primary outcome was all-cause mortality at final follow-up. Results: We included 13 trials enrolling 5268 patients. Compared with usual care, EGDT was associated with decreased mortality (risk ratio [RR]: 0.87, 95% CI: 0.77-0.98; 4664 patients, 8 trials; Grading of Recommendations Assessment, Development, and Evaluation [GRADE] quality of evidence was moderate). Compared with lactate clearance–guided therapy, EGDT was associated with increased mortality (RR: 1.60, 95% CI: 1.24-2.06; 604 patients, 5 trials; GRADE quality of evidence was low). Patients assigned to EGDT received more intravenous fluid, red cell transfusion, vasopressor infusion, and dobutamine use within the first 6 hours than those assigned to usual care (all P values < .00001). Conclusion: Adults with severe sepsis and septic shock who received EGDT had a lower mortality than those given usual care, the benefit may mainly be attributed to treatments administered within the first 6 hours. However, the underlying mechanisms by which lactate clearance–guided therapy benefits these patients are yet to be investigated.